2017
DOI: 10.1002/pi.5375
|View full text |Cite
|
Sign up to set email alerts
|

Peptide‐functionalized reduced graphene oxide as a bioactive mechanically robust tissue regeneration scaffold

Abstract: Bioactive, synthetic materials represent next-generation composites for tissue regeneration. Design of contemporary materials attempts to recapitulate the complexities of native tissue; however, few successfully mimic the order in nature. Recently, graphene oxide (GO) has emerged as a scaffold due to its potential for bioactive functionalization and long-range order instilled by the self-assembly of graphene sheets. Chemical reduction of GO results in a more compatible material with enhanced properties but com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 63 publications
(74 reference statements)
1
17
0
Order By: Relevance
“…However, we have previously shown that the DLS‐determined Z‐average diameter reasonably agrees with the particle dimensions measured using high‐resolution optical microscopy, atomic force microscopy, and scanning electron microscopy. [ 66–70 ] Thus, for experimentally relevant micron‐sized sheets of GO, settling will dominate.…”
Section: Resultsmentioning
confidence: 99%
“…However, we have previously shown that the DLS‐determined Z‐average diameter reasonably agrees with the particle dimensions measured using high‐resolution optical microscopy, atomic force microscopy, and scanning electron microscopy. [ 66–70 ] Thus, for experimentally relevant micron‐sized sheets of GO, settling will dominate.…”
Section: Resultsmentioning
confidence: 99%
“…98,99 On the other hand, GDs could be further endowed with new functions by binding with active substances. [100][101][102] In this subsection, we reviewed the different functional groups of GDs modification in bone repair materials and the progress had been made in the properties and functions of the composites. Then, GDs were bound with different active substances such as peptides and drugs, and which functions of bone repair materials were improved by in vitro and in vivo experiments.…”
Section: Large Specific Surface Area (Ssa) and Easy Modificationmentioning
confidence: 99%
“…Scaffold showed enhanced neurite sprouting and angiogenic restoration.103Nano GOAdipose stem cellsAppropriate biodegradation with a lower inflammatory reaction in in vivo analysis.104Nano GOBone cellsImproved thermal stability, cytocompatibility, osteo-bioactivity, and biodegradability.105GrapheneNeural stem cellsNeural proliferation, stimulation, induced differentiation of stem cells, degradability, and implantable neuronal networks.106Graphene nanoflakesMesenchymal stem cells (MSCs)Cell viability, proliferation and significant upregulation of both osteogenic and neurogenic gene expression.107Single layer GrapheneHuman MSCs (hMSCs)Graphene accelerated cell adhesion to the substrate without affecting cell proliferation. Graphene promotes osteogenic differentiation by protein upregulation.108RGO nanomeshHuman neural stem cells (hNSCs)Good chemical stability, excellent cell differentiation, good proliferation, and differentiation to neural cells.109GO and RGO hydrogelMyoblasts (C2C12)RGO hydrogel exhibited superior proliferation, myogenic differentiation and increased myogenic gene expression compared with GO hydrogel.110GO fiber matHuman osteoblast cell line (SAOS-2)High tensile strength, modulus and enhanced cell proliferation.111RGO hydrogelCardiomyocytesImproved cell viability, proliferation, and maturation.112RGOWister rat peritoneal macrophage cellsAntibacterial, antifungal, and biocompatible to macrophage cells.113RGOFibroblasts (NIH-3T3) and macrophages (RAW 264.7)Biocompatible, biodegradable, and bioactive.114GO, RGO…”
Section: Graphene and Its Derivatives In Cell And Tissue Engineeringmentioning
confidence: 99%
“…Combining RGO with natural bone mineral, nano-HA (nHA), which has excellent properties such as osteoconductivity and osteoinductivity, resulted in the design of a self-assembled biomimetic 3D scaffold suitable for bone tissue engineering. The porous 3D scaffold made by Nie et al,114 was investigated on in vivo bone repair efficiency, accentuating the impacts of the graphene composite on in vivo bone cell growth and mineralization. Interestingly, compared to RGO, the RGO-nHA based biomimetic 3D scaffold showed enhanced cell proliferation, alkaline phosphatase (ALP) activity, and excellent osteogenic potential.…”
Section: Graphene and Its Derivatives In Cell And Tissue Engineeringmentioning
confidence: 99%